Critical congenital heart disease screening - Mohammed A Chamsi-Pasha (Thieme Medical and Scientific Publishers Pvt. Ltd., 2016)
Critical congenital heart disease (CCHD) is a heart lesion for which neonates require early surgical intervention to survive. Without intervention, the rates of mortality and survival with significant disability are extremely high. Early diagnosis can potentially improve health outcomes in newborns with CCHD. Until recent years, no routine screening protocol existed. In the last few years, pulse oximetry screening for CCHD in newborns has been added to the list of recommended uniform screening panels and advocated by several health-care authorities. A positive screening test result warrants an echocardiogram to evaluate for CCHD. Newborn screens do not usually require parental consent. However, most of the states mandates in the United States include a statement allowing exemption from the screen on the basis of parental religious or personal beliefs.